Letter from J.E.C. Donnelly to James Connolly requesting that Connolly write a response to an article entitled 'The Appeal to Reason' regarding "senseless attacks which are being made upon the Socialist movement by some so-called Catholic papers", - Donnelly, J. E. C. (1908)
Donnelly enclosed two articles whicha re no longer extant.